Effect of Salt (Nacl) and Vacuum Packaging on Some of the Quality Attributes of Snakehead Fish - Eka Andriani; Hendrik Septiana; Al Mukhlas Fikri (International Journal of Food Studies)
Snakehead fish (Chana striata) is one of the important protein sources among Indonesian people. However, the shelf life is short leading to limited use of fresh snakehead fish. This study aimed to analyse the effect of vacuum packaging and addition of salt on the sensory properties, total plate count, water activity and pH of fresh snakehead fish. The fish was salted (NaCl) at various concentrations, including 0, 5, 10 and 15%, and kept for 14 days at refrigeration temperature (± 3°C). Sensory evaluation, total plate count (TPC) and water activity (aw) measurements, and pH analysis were performed at day 0, 7 and 14. All groups with salt addition exhibited a significantly slower decrease in the mean scores (9-point hedonic scale) of color, aroma, appearance and texture (p < 0.05), with the decrease for all sensory properties detected at day 7 of storage. In microbial tests, a significant increase in TPC was observed in the groups with 0% and 5% salt addition (p < 0.05). The group with 15% salt addition showed the lowest water activity. Also, the group without salt addition had the highest pH value. This study demonstrated that addition of salt to snakehead fish might gives beneficial effects on the shelf life of a vacuum packaged product. However, the optimum shelf life using vacuum packaging and salt addition needs further study.